Identifying adopters and non-adopters of Broadband amongst silver surfers: using BHPS. (27th December 2010) - Choudrie, Jyoti; Grey, Susan; Haslam, Colin; Tsitsianis, Nicholas
The aim of this paper is to identify the adopters and non-adopters of Broadband within the silver surfer group. This was achieved using the British Household Panel Survey, a large scale survey used to collect data from UK households. The data was analysed using statistical tools, such as, SPSS v. 15. The conclusions drawn are that Broadband will be adopted in nuclear households (no presence of elderly) with silver surfers who have children aged between 12 and 18, without ignoring the role played by a relatively level of education. This research offers contributions for academics by providing an objective viewpoint of the factors leading to Broadband adoption within silver surfers, a group of immense, current interest. For industry, this research offers an intensive identification of socio-economic factors that are considered important when marketing a product or service within the market.